The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00438-016-1275-z
|View full text |Cite
|
Sign up to set email alerts
|

The ferredoxin-dependent glutamate synthase (OsFd-GOGAT) participates in leaf senescence and the nitrogen remobilization in rice

Abstract: Ferredoxin-dependent glutamate synthase (Fd-GOGAT, EC 1.4.7.1) plays major roles in photorespiration and primary nitrogen assimilation. However, due to no mutant or knockdown lines of OsFd-GOGAT have been reported in rice (Oryza sativa L.), the contribution of OsFd-GOGAT to rice foliar nitrogen metabolism remains little up-to-date. Here, we isolated a rice premature leaf senescence mutant named gogat1, which was reduced in 67% of the total GOGAT enzyme activity in leaves. The gogat1 mutant exhibited chlorosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Meanwhile, the gogat1 mutant showed a reduced seed setting rate and increased grain protein and amino acid content. This result showed that OsFd-GOGAT plays an important role in nitrogen remobilization during leaf senescence [ 41 ].…”
Section: Nitrogen Remobilization Involved In Rice Leaf Senescencementioning
confidence: 99%
“…Meanwhile, the gogat1 mutant showed a reduced seed setting rate and increased grain protein and amino acid content. This result showed that OsFd-GOGAT plays an important role in nitrogen remobilization during leaf senescence [ 41 ].…”
Section: Nitrogen Remobilization Involved In Rice Leaf Senescencementioning
confidence: 99%
“…A recent work of Zeng et al [38] showed how a single nucleotide polymorphism, leading to an aminoacid substitution in rice Fd-GOGAT genes, resulted in an increased GPC, confirming its important role as a potential candidate in NUE improvement. The NADH-GOGAT gene was also identified as a major candidate gene for cereal NUE by a cross-genome ortho-meta QTL study of NUE [39].…”
Section: Gogat Allelic Variants and Relationship With Gpcmentioning
confidence: 99%
“…OsFd-GOGAT is highly abundant in mesophyll cells and other chloroplast-containing cells regulated by light [56] and is important in reassimilation of ammonium generated by photorespiration in chloroplasts [65]. Recently, participating in nitrogen assimilation, C/N balance, [66], leaf senescence, and the nitrogen remobilization has been reported [67]. OsNADH-GOGAT1 is mainly expressed in surface cells of rice roots in an NH 4 + -dependent manner and is important for primary ammonium assimilation in roots at the seedling stage and development of active tiller number until the harvest [62,65].…”
Section: Nitrogen Assimilationmentioning
confidence: 99%